RUMAH SEHAT DAN KENYAMANAN TERMAL PENCEGAHAN PENULARAN COVID-19 - Mustamin, Tayeb; Quraisy, Sayyid; Nasrullah, Nasrullah; Faharuddin, Ansarullah; nasrun, ardi (LPPM UNIVERSITAS KHAIRUN, 2024)
Abstract According to Winslow and APHA, a healthy home is defined as a place to live permanently. Serves as a place to live, rest, recreation (relax) and as a shelter from environmental influences that meet physiological, psychological requirements and are free from disease transmission. Too many occupants can increase the risk of transmission of infectious diseases. The house is a physical structure consisting of rooms, courtyards and the surrounding area which is used as a place to live and a means of fostering a family (RI Law No. 4 of 1992). According to WHO, a house is a physical structure or building for shelter, where the environment is useful for physical and spiritual health and social conditions for both the health of families and individuals. (WHO Commission on Health and the Environment, 2001).Objective: Increase the understanding of the people of Tadenas Village regarding the importance of healthy homes and thermal comfort as well as the health effects arising from housing conditions that do not meet predetermined standards. Methods: Conduct situation analysis, problem prioritization, instrument development, and determinant surveys related to healthy homes. The intervention was carried out for the community in the Tadenas Village by measuring temperature, humidity and wind speed. Then an assessment is carried out through the results of measurements and standards that should be so that it becomes a healthy home.Results: The low implementation of healthy housing in Tadenas Village is caused by a lack of knowledge and attitudes of the community towards the importance of meeting housing conditions standards.Conclusion: Based on measurements with lower middle class housing conditions, the knowledge and attitude of the community towards the importance of fulfilling standard housing conditions to achieve a healthy home is still very low